2017
DOI: 10.1088/1361-6528/aa57b5
|View full text |Cite
|
Sign up to set email alerts
|

MEAs and 3D nanoelectrodes: electrodeposition as tool for a precisely controlled nanofabrication

Abstract: Microelectrode arrays (MEAs) are gaining increasing importance for the investigation of signaling processes between electrogenic cells. However, efficient cell-chip coupling for robust and long-term electrophysiological recording and stimulation still remains a challenge. A possible approach for the improvement of the cell-electrode contact is the utilization of three-dimensional structures. In recent years, various 3D electrode geometries have been developed, but we are still lacking a fabrication approach th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…By depositing 10 nm of alumina inside these pores and then etching away the surrounding polycarbonate, they were able to form hollow nanostraws . Others have combined track‐etched membranes (or photoresist templates) with electrodeposition to fabricate solid nanoelectrodes . This approach benefits from being able to readily and rapidly pattern large areas, with the downside of a relative lack of control over nanostraw placement and distribution uniformity.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…By depositing 10 nm of alumina inside these pores and then etching away the surrounding polycarbonate, they were able to form hollow nanostraws . Others have combined track‐etched membranes (or photoresist templates) with electrodeposition to fabricate solid nanoelectrodes . This approach benefits from being able to readily and rapidly pattern large areas, with the downside of a relative lack of control over nanostraw placement and distribution uniformity.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…Both techniquese allow for the creation of create vertical structures with two different conductive layers (Nick, Thielemann, and Schlaak 2014). In the case of electrodeposition, depending on the lithographic pattern, a variety of geometries (Jahed et al 2014) can be fabricated as shown in the work of Weidleich et al, for instance, where solid and hollow-like structures were created by finely controlling gold electrodeposition (Figure 1A) (Weidlich et al 2017). Fabrication of structures which protrude vertically from a support material can utilize imprinting and etching processes.…”
Section: Fabricationmentioning
confidence: 99%
“…A large number of substrate materials have been successfully used to fabricate MEAs and facilitate cell adhesion, including silicon dioxide (Mastrototaro et al, 1992), silicon nitride (Connolly et al, 1990), SU-8 (Y. , polystyrene (Hammack et al, 2018), parylene (Charkhkar et al, 2016(Charkhkar et al, , 2012Omaki et al, 2017), liquid crystal elastomer (Rihani et al, 2018), and others. Reduction in electrode impedance is dependent on several factors, but recent advances in electrodeposition, metallic 3D printing, and electrospinning have enabled nanofabrication of electrode sites; potentially enhancing longterm cell-to-electrode coupling and effectively reducing electrode impedance, resulting in increased signal-to-noise ratios (Heim et al, 2012;Jao et al, 2015;Krishnamoorthy and Zoski, 2005;Santoro et al, 2014;Weidlich et al, 2017).…”
Section: Substrate-integrated Microelectrode Arrays-similarmentioning
confidence: 99%